PROPAGATION CURVES AND PATHLOSS EVALUATION FOR UHF WAVE (CHANNEL 22, 479.25MHz) WITHIN KATSINA METROPOLIS - Akinbolati, Akinsanmi; Joseph, E.; Okpala, C. (FUDMA JOURNAL OF SCIENCES, 2023)
Propagation curve is the variation of the electric field strength of a radio signal with distance whereas signal path loss is essentially the reduction in power density of an electromagnetic wave or signal as it propagates through the environment in which it is travelling. In view of the importance of television broadcasting to the socio-economic development of the populace and the competition of the business in Nigeria, researches that can enhance Quality of Service(QoS) from broadcasting stations have become necessary to radio scientists. The aim of this research is to determine the propagation curves and path loss for Katsina State Television (KTTV) Signal within Katsina metropolis. Measurement of the signal strength was done at an interval of 1km Line of Sight (LOS) using a signal level meter along three radial routes from the transmitter with each route spanning up to 15km . A GPS hand held receiver was used to record the LOS, longitude, latitude and the elevation of the data locations. The three radial routes are route A from KTTV Base station (in Katsina) towards Batsari, route B, KTTV Base station towards Daura and route C from KTTV Base station towards Dutsinma. The signal strength values were used to plot the propagation curves along the routes of measurements. In addition, the data obtained were used equally used to evaluate the path loss using the well acceptable Okumura- Hata model for macro cell prediction. The result of the study shows that signal strength reduces with distance along the three
Keywords: Path loss Evaluation, Propagation, UHF and Katsina